Neurological Complications in Patients with Heart Transplantation - Sakusic, Amra; Rabinstein, Alejandro A. (Seminars in Neurology, 2021)
Neurological complications after heart transplantation are common and include cerebrovascular events (ischemic strokes, hemorrhagic strokes, and transient ischemic attacks), seizures, encephalopathy, central nervous system (CNS) infections, malignancies, and peripheral nervous system complications. Although most neurological complications are transient, strokes and CNS infections can result in high mortality and morbidity. Early recognition and timely management of these serious complications are crucial to improve survival and recovery. Diagnosing CNS infections can be challenging because their clinical presentation can be subtle in the setting of immunosuppression. Immunosuppressive medications themselves can cause a broad spectrum of neurological complications including seizures and posterior reversible encephalopathy syndrome. This article provides a review of the diagnosis and management of neurological complications after cardiac transplantation.
Keywords: neurological complications; heart transplantation; cerebrovascular events; central nervous system infections; seizures